2020
DOI: 10.3389/fpls.2020.573272
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nitrogen Deficiency Inversion in Rice Leaves Based on the Hyperspectral Reflectance Differential

Abstract: To achieve rapid, accurate, and non-destructive diagnoses of nitrogen deficiency in cold land japonica rice, hyperspectral data were collected from field experiments to investigate the relationship between the nitrogen (N) content and the difference in the spectral reflectance relationship and to establish the hyperspectral reflectance difference inversion model of differences in the N content of rice. In this study, the hyperspectral reflectance difference was used to invert the nitrogen deficiency of rice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…P deficiency reduces Pi concentration in the chloroplast, inhibits ATP synthase activity and consequently affects the electron transport chain, resulting in the transient change of chlorophyll a fluorescence [ 29 ]. A recent study developed a model to predict N content of rice using the leaf hyperspectral profile and suggested that collecting reference spectral reflectances and reference N content of rice at various developmental stages would be necessary to accurately evaluate the N status of rice [ 37 ]. These findings indicated that several factors, such as plant growth stages and the measured biochemical and physiological parameters, could have a significant impact on the reported R 2 statistics in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…P deficiency reduces Pi concentration in the chloroplast, inhibits ATP synthase activity and consequently affects the electron transport chain, resulting in the transient change of chlorophyll a fluorescence [ 29 ]. A recent study developed a model to predict N content of rice using the leaf hyperspectral profile and suggested that collecting reference spectral reflectances and reference N content of rice at various developmental stages would be necessary to accurately evaluate the N status of rice [ 37 ]. These findings indicated that several factors, such as plant growth stages and the measured biochemical and physiological parameters, could have a significant impact on the reported R 2 statistics in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key objectives of agricultural production was to maximize crop yields with minimal fertilizer inputs [56,57]. K is a macronutrient element necessary for apple production [38,58].…”
Section: Comparison Of Models and Determination Of Optimum K Ratementioning
confidence: 99%
“…The leaves were first sampled and then placed in a HSI system. Yu et al (2020) developed leaf-level nitrogen content models from spectral data on a single japonica variety and a single indica variety under field conditions. Their canopy-level HSI data was collected with a spectroradiometer, and Vegetation Indices were used as model input.…”
Section: Introductionmentioning
confidence: 99%